The three-body abrasive tribological characteristics of the Graphene/h-BN heterostructure film considering defects. (July 2022) - Zhao, Bo; Zhang, Yutao; Fan, Yuyan; Yu, Xiaotong; Zhang, Zhinan; Zhang, Baocheng
Abstract: The heterostructure film composed of graphene and h -BN performs excellently in friction-reduction, wear-resistance and long-term corrosion resistance, which offers a promising solution for achieving long service life in marine applications. In this study, the three-body abrasive tribological characteristics of the heterostructure film are investigated with molecular dynamics simulations. Three typical kinds of point defects, as well as two kinds of large multi-vacancy defects with different configurations, are investigated to characterize their influence on the three-body tribological performance of the heterostructure film. Results show the self-rotation of the rolling abrasive is conductive to reducing the friction resistance and occurrence of the wear. This study provides an atomic-level understanding on the tribological characteristics of the heterostructure film composed of graphene and h -BN. Highlights: A "Rolling" command is developed in LAMMPS to achieve the three-body sliding contact simulation in nano-scale. Various point defects in the heterostructure film are investigated to reveal their effects on the three-body abrasion. Two kinds of multi-vacancy defects are investigate to characterize their influence on the three-body abrasion of the heterostructure film.